Makna dan Gaya Hidup: Studi Fenomenologi Olahraga Padel pada Masyarakat Kota Bandung - Rafika Mutiara Guniarti; Tatang Muhtar; Rizal Ahmad Fauzi; Anggi Setia Lengkana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to explore the subjective experiences, phenomenological meanings, and motives for the involvement of the people of Bandung City in the sport of padel. Using a qualitative approach with a phenomenological design, this study involved 50 informants consisting of 20 active players, 10 coaches, 10 field managers, and 10 non-participants selected through purposive sampling. Data were collected through in-depth interviews, passive participatory observation, and digital documentation studies, then analyzed using NVivo software through open coding, axial coding, and selective coding stages. The study found four main findings: (1) The construction of meaning of padel is formed through four dimensions health, recreation, social space, and urban lifestyle identity; (2) Players lived experience is built through a process of social introduction, regular playing routines, community interaction, and internalization of padel as a lifestyle; (3) Involvement is driven by because motive (social homophily and FOMO) that transitions into in-order-to motive (networking, health, personal branding); (4) There are massive symbolic consumption practices and social distinctions that create upper-middle-class exclusivity. It is concluded that padel in Bandung City is not merely a temporal sports trend, but rather an arena of lifestyle commodification that reproduces the social boundaries of urban communities. Keywords: Social Distinction, Phenomenology, Urban Lifestyle, Meaning Construction, Padel Sport